Secondary Brain Lymphoma in a Case of Breast Diffused Large B-Cell Lymphoma: Case Report - Javadian, Hamed; Jalili Khoshnood, Reza; Shahmohammadi, Mohammad Reza; Hosseini, Seyed Amir Hassan; Keikhaee, Mohsen (International Clinical Neuroscience Journal, 2018)
Secondary central nervous system lymphoma (SCNSL) is known as a rare disease. The risk factor of developing SCNSL is primary lymphoma type and site of involvement. We present a patient with an altered mental status known case of breast diffused large B-cell lymphoma (DLBCL) who underwent stereotactic biopsy because of a left periventricular mass lesion, which diagnosed as secondary brain lymphoma after pathologic typing. Because of limited data about the secondary central nervous system, lymphoma and it is a risk factor, we reported an aggressive breast DLBCL with brain involvement.